2020
DOI: 10.1007/s11696-020-01295-y
|View full text |Cite
|
Sign up to set email alerts
|

New hybrids of tacrine and indomethacin as multifunctional acetylcholinesterase inhibitors

Abstract: A new series of hybrid compounds were designed, consisting of anti-AChE and BuChE activity components with an antiinflammatory component. A series of 9-amino-1,2,3,4-tetrahydroacridine and indomethacin derivatives were synthesized. All compounds were created using alkyldiamine with different chain lengths as a linker. Various biological activities were evaluated, including inhibitory activity against AChE and BuChE. The tested compounds showed high inhibitory activities against cholinesterases. The IC 50 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The IC 50 values thus obtained are 33 µM and 2.5 µM for AChE and BChE, respectively. This can be compared to the IC 50 values of the reference inhibitors: Rivastigmine was was reported to have an IC 50 value in AChE of 71µM [42] or 501 µM [43], whereas for Tacrine the values range between 0.2-0.45 µM [44,45]. Ondansetron is hence a more potent binder to AChE than Rivastigmine, but less so than Tacrine, which agrees perfectly with the MMGBSA data of Table 2.…”
Section: A Of Ondansetron In the Enzymessupporting
confidence: 74%
“…The IC 50 values thus obtained are 33 µM and 2.5 µM for AChE and BChE, respectively. This can be compared to the IC 50 values of the reference inhibitors: Rivastigmine was was reported to have an IC 50 value in AChE of 71µM [42] or 501 µM [43], whereas for Tacrine the values range between 0.2-0.45 µM [44,45]. Ondansetron is hence a more potent binder to AChE than Rivastigmine, but less so than Tacrine, which agrees perfectly with the MMGBSA data of Table 2.…”
Section: A Of Ondansetron In the Enzymessupporting
confidence: 74%
“…The IC 50 values thus obtained are 33 µM and 2.5 µM for AChE and BChE, respectively. This can be compared to the IC 50 values of the reference inhibitors: Rivastigmine was reported to have an IC 50 value in AChE of 71 μM 45 or 501 μM 46 , whereas for Tacrine the values range between 0.02 and 0.45 μM 46,47 .…”
Section: Resultsmentioning
confidence: 99%
“…Because the number of articles devoted to the development of analogues of THA is enormous, we structured the articles published in 2006–2022 [ 30 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 …”
Section: Summary Of Tacrine-based Hybrids Reported In 2006–2022mentioning
confidence: 99%
“…In 2021, Zawada et al reported THA–indometacine hybrids 464 – 471 [ 77 ]. The IC 50 values for hybrids range from 10 to 260 nM.…”
Section: Tacrine Hybrids With Biological Active Organic Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation